The Effect Of “The Venn Diagram” As A Cooperative Learning Strategy to Improve Reading Comprehension in Legal Description Texts During the Covid-19 Pandemic Period: As a Simple Quasy Experimental Approach With A Non Equivalent Control Group in English Spesific Purpose Design For the Sariah Faculty of Constitutional Law - Ferri Susanto (Edu-Ling: Journal of English Education and Linguistics, 2021)
The research was to find the simple effect of a graphic organizer which is one of the cooperative learning strategies by using Venn diagrams to improve reading comprehension of descriptive texts in English class for Law IAIN Bengkulu. The Venn Diagram has a positive effect on students. The research is Quays experimental with a non-equivalent control group design in English Specific Purpose for Law. The populations were second-semester students of the Faculty of Law. They are class A consisting of 16 students as an experimental class (international class) and class B consisting of 16 students (international class) as a control class. The totality sample is used, the researcher took the sixth step, namely; first, students were given Pre-Test for both classes to determine the experimental and the control class. Second, giving treatment for three meetings in the experimental and control classes. Third, the researcher conducted a Post-Test, in the experimental and control classes to determine the effect of the Venn Diagram. Fourth, the researcher analyzed the test using the assessment criteria. Fifth, the researcher used the t-test formula to determine the significance of the use of it from the experimental class. Sixth discusses conclusions based on the data. The results indicate that Venn Diagrams can improve students' understanding of reading descriptive texts. It can be seen after being calculated by the T-test formula that the T-Count is higher than the T-table (2.25 > 2.0423) and the average value of the two classes increased by about 9.68 points for the experimental class and 2.19 points for the control class that it has a positive effect on students' law. Furthermore, suggested that the Venn diagram is applied by students for reading comprehension.